Debate - The Trafficking Protocol has Advanced the Global Movement against Human Exploitation: The case of the United Kingdom - Parkes, Caroline (Anti-Trafficking Review, 2015)
When politicians, responding to public campaigns focused on human trafficking, make bold and over-emotive statements, invoking William Wilberforce and the pressing need to lead the global fight against slavery, the Trafficking Protocol,[1] proves its worth. Insulated from national political rhetoric, international treaties, be it the Trafficking Protocol or regional instruments, provide an invaluable structure for governments’ national legislative responses to human trafficking. As the United Kingdom’s (UK) Solicitor General noted,[2] The UK’s legal framework has been directly influencedby UN [United Nations] and EU [European Union] Conventions and Directives (emphasis added) … [and] The ‘Palermo Protocol’ continues to shape the UK’s response to human trafficking and in particular the care and support afforded to identified human trafficking victims. [1] In full: Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children. [2] Speech, Solicitor General, Oliver Heald QC MP, ‘Prosecuting human trafficking and slavery: The law and the UK response’, UK Government, 12 October 2012, retrieved 6 January 2015 https://www.gov.uk/government/speeches/prosecuting-human-trafficking-and-slavery-the-law-and-the-uk-response